Inclusive semileptonic Λ b decays in the Standard Model and beyond - P. Colangelo; F. De Fazio; F. Loparco (Journal of High Energy Physics, 2020)
Abstract Inclusive semileptonic decays of beauty baryons are studied using the heavy quark expansion to O 1 / m b 3 $$ \mathcal{O}\left(1/{m}_b^3\right) $$ , at leading order in α s . The case of a polarized decaying baryon is examined, with reference to Λ b . An extension of the Standard Model effective Hamiltonian inducing b → U ℓ ν ¯ ℓ $$ U\mathrm{\ell}{\overline{ν}}_{\mathrm{\ell}} $$ transitions (U = u, c and ℓ = e, μ, τ) is considered, which comprises the full set of D=6 semileptonic operators with left-handed neutrinos. The effects of the new operators in several observables are described.